Assessment of Kisan Mobile Advisory (KMA) Service for Dissemination of Agricultural Information in Mehsana District of Gujarat State - Patel, M. R.; Patel , M. V.; Patel, R. A. (Indian Journal of Extension Education, 2017)
In present scenario, agriculture being highly skill oriented technically intensive needed a high priority. At present the  ratio of farmers to extension worker is quite low (1000:1). Maximum RAEO or other extension workers disseminated  agriculture knowledge without having much accountability and expertise. This issue has created a gap between improved  agriculture technology and the end user (farmer). To address the issue Kisan Mobile Advisory Service was launched for  sending information through SMS in Mehsana District through Krishi Vigyan Kendra during January 2014. The content  of messages were typed in Gujarati language and information related to crop production, crop protection, vegetable and  fruit production, spice crops, dairy farming, weather forecasting, post harvest management and other agricultural and  allied related information sent to end users. To evaluate and information and usefulness of information, the present study  was conducted with survey of 80 farmers, 10 in-service personnel and 10 input suppliers of district during 2014-15. The  result of survey shows that messages were highly understandable for majority (42.50 %) of the farmers. It was highly  understandable for 80 per cent and 50 per cent KMA member of in-service personnel and input supplier category,  respectively. The messages were needful and timely for 67.50 per cent of KMAmember of farmers’category and about 70  per cent and 50 per cent for in-service personnel and input supplier, respectively. As far as applicability of message is  concerned, messages were fully applicable for about 44 per cent of KMAmember of farmers’ category whereas medium  and partially applicable were reported by 17.50 per cent and 22.50 per cent of members, respectively. It was also found  that messages were fully applicable for in-service personnel (60 %) and input supplier (50 %). Majority of the farmers  (72.50 %) conveyed the messages minimum to at least another farmer in social system.
Keywords: KMA; SMS; RAEO; ICTmobile